Isolation of microorganisms involved in reduction of crystalline iron(III) oxides in natural environments - Hori, Tomoyuki; Aoyagi, Tomo; Itoh, Hideomi; Narihiro, Takashi; Oikawa, Azusa; Suzuki, Kiyofumi; Ogata, Atsushi; Friedrich, Michael W.; Conrad, Ralf; Kamagata, Yoichi (Frontiers in Microbiology, 2015)
Reduction of crystalline Fe(III) oxides is one of the most important electron sinks for organic compound oxidation in natural environments. Yet a limited number of isolates makes it difficult to understand physiology and ecological impact of the microorganisms involved. Here, two-staged cultivation was implemented to selectively enrich and isolate crystalline iron(III) reducers in soils and sediments. Firstly, iron reducers were enriched and other untargeted eutrophs were depleted by two-year successive culture on a crystalline ferric iron oxide (i.e., goethite, lepidocrocite, hematite, or magnetite) as electron acceptor. Fifty-eight out of 136 incubation conditions allowed the continued existence of microorganisms as confirmed by PCR amplification. High-throughput Illumina sequencing based on 16S rRNA genes revealed that the enrichment cultures on each of the ferric iron oxides contained bacteria belonging to the Deltaproteobacteria (mainly Geobacteraceae), followed by Firmicutes and Chloroflexi, which also comprised most of the operational taxonomic units (OTUs) identified. The Venn diagrams indicated that the core OTUs enriched with all of the iron oxides were dominant in the Geobacteraceae. Secondly, 38 enrichment cultures including novel microorganisms were transferred to soluble-iron(III) media in order to stimulate proliferation of the enriched iron reducers. Through extinction dilution-culture and single colony isolation, six strains within the Deltaproteobacteria were finally obtained; five strains belonged to the genus Geobacter and one strain to Pelobacter. These isolates had 94.8–98.1% sequence similarities of 16S rRNA genes to cultured relatives. All the isolates were able to grow on acetate and ferric iron but their physiological characteristics differed considerably in terms of growth rate. The results demonstrate the successful enrichment and isolation of novel iron(III) reducers that were able to thrive by reducing highly crystallized ferric irons.